Recent efforts and advances towards sustainable ceramics made from textile wastes- A review - Vinay Kumar Chauhan; P. Thennarasu; Ragini Dubey; Shiwanand Pandey; Ram Naresh (Open Ceramics, 2023)
Environmental and public health problems have been linked to the accumulation of waste products from a variety of industrial and energy production operations. The way that trash is recycled is where ceramics really stand out. Research is being conducted to determine whether or not “certain wastes and industrial by-products, such as fly ash (FA), rice husk ash (RHA), blast furnace slag (BFS), sludge, glass waste, polished tile waste, eggshell, textiles and others, might be used in the production of ceramics. According to the findings of the research, there is a great possibility for the ceramic sector to use wastes as a substitute for natural raw materials in the production process. Converting waste products into valuable ceramics is an environmentally responsible solution to address problems associated with waste management.